A Gendered Lens for Genocide Prevention (Rethinking Political Violence, 2018)
'This volume brings an important new perspective to the field of genocide prevention. I highly recommend it.' Deborah Mayerson, Research Fellow, University of Wollongong, Australia This edited collection develops a gendered lens for genocide prevention by uncovering socially constructed gender roles which are crucial for the onset, form and prevention of genocide and mass atrocities. This volume draws on contemporary feminist theory, concepts of masculinity, critical discussions of international law, and in-depth case studies to provide a better understanding of the function of gender at different stages of genocide and mass atrocity processes as well as a basis for more comprehensive strategies for genocide prevention.